Investigating candidate genes for an association with skin color pattern in the mimic poison frog Ranitomeya imitator - White, Emily D (East Carolina University)
Understanding the genetic basis of adaptive traits can help us better understand their evolution. The mimic poison frog, Ranitomeya imitator, is native to Peru. Like many other species of poison frogs, it has aposematic coloration to warn predators of its toxicity, so that its dorsal color pattern is directly linked to its survival. Recently, R. imitator has undergone a mimetic radiation, in which it has evolved to mimic three species of congeneric poison frogs. This mimicry has caused a divergence of color pattern within R. imitator, giving rise to four different color pattern morphs (striped, spotted, banded, and varadero). In this thesis, the main objective is to investigate the genetic basis of this phenotypic divergence. Here, we focus specifically on investigating candidate color pattern genes in the striped and banded morphs, which differ mainly in their dorsal color (yellow to orange), hindlimb color (green to orange), and their dorsal pattern (striped to banded). To do this, we formed a lab-reared pedigree by crossing two morphs of R. imitator (striped and banded) for two generations. For each individual in the pedigree, we amplified each candidate gene (asip, mc1r, bsn, and retsat) and sequenced them via Sanger sequencing. To determine phenotypes, we took spectral reflectance measurements and photos of each frog. We analyzed and summarized spectral reflectance data using the PAVO package in R. The photos were analyzed using a program written by Tyler Linderoth, which quantifies the orientation of the dorsal stripes/bands. We used the program Merlin to test for a genotype-phenotype association. Our tests indicated associations between genotype and color pattern phenotypes for all four candidate genes tested. Our results show that these genes are promising candidates for controlling aspects of skin color pattern in R. imitator. Further study of these genes will help elucidate the proximate mechanisms of phenotypic divergence in R. imitator, giving us a better understanding of the evolution of aposematism in this species and potential insights into the molecular basis of skin color pattern more generally.
Keywords: Dendrobatidae--Peru; Mimicry (Biology); Animal communication; Gene expression